2001
DOI: 10.1021/ol016310j
|View full text |Cite
|
Sign up to set email alerts
|

Radical [3 + 2] Annulation of N-Allyl-N-chlorotosylamide with Alkenes via Atom-Transfer Process

Abstract: [reaction: see text]. A radical [3+2] annulation reaction with an N-centered radical has been developed. The reaction of alkenes with N-allyl-N-chlorotosylamide yields the corresponding pyrrolidine derivatives in good yields in the presence of Et3B as a radical initiator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 10 publications
1
27
0
Order By: Relevance
“…In the case of 17 , the sterically more hindered cis isomer is the major isomer, which is again consistent with the Beckwith–Houk model . It is noteworthy that in a related [3+2] cycloaddition reported by Tsuritani, Shinokubo, and Oshima, the authors reported a 68:32 d.r . in a similar reaction albeit with a considerable lower yield of 28%.…”
Section: Resultssupporting
confidence: 83%
“…In the case of 17 , the sterically more hindered cis isomer is the major isomer, which is again consistent with the Beckwith–Houk model . It is noteworthy that in a related [3+2] cycloaddition reported by Tsuritani, Shinokubo, and Oshima, the authors reported a 68:32 d.r . in a similar reaction albeit with a considerable lower yield of 28%.…”
Section: Resultssupporting
confidence: 83%
“…In 2001, Oshima and co-workers reported an elegant radical [3+2] annulation of alkenes with N-allyl-N-chlorotosylamide (1) as N-radical precursor for the preparation of pyrrolidine derivatives 2 (Scheme 2). 46 This cascade proceeds through a radical chain process and features a broad scope with respect to the alkene component. Hence, aliphatic alkenes, styrenes, vinyl acetates and even benzofuran are eligible acceptors yielding the corresponding multi-substituted pyrrolidines in high yields albeit with low diastereoselectivity.…”
Section: Radical 21-carboamidation Of Alkenesmentioning
confidence: 99%
“…Other procedures for the synthesis of these compounds including N -chlorination with an fivefold excess of Oxone ® in the presence of NaCl/Al 2 O 3 [ 35 ] or deprotonation and reaction with NCS [ 36 37 ] did not lead to higher or led in distinctly lower yields to the N -chloro compounds.…”
Section: Resultsmentioning
confidence: 99%